Ilocutionary Speech Acts in the Song Lyrics of the Fabula Album by Mahalini and Its Relevance as Indonesian Language Teaching Materials in Senior High School - Riana, Helma; Wahyudi, Agus Budi (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
This study aims to describe the form of illocutionary speech acts in the lyrics of Fabula album by Mahalini and its relevance as Indonesian language teaching materials in high school. The method used is descriptive qualitative. The research data is in the form of fragments of Fabula album song lyrics and the data source is a collection of Mahalini's song lyrics in the Fabula album. Data collection was done by listening and note taking techniques. Data analysis was carried out using the commensurate and agih methods. The results showed that there are 35 data included in the illocutionary speech acts which are assertive, directive, expressive, and commissive. While the functions of illocutionary speech acts found are the function of asking, the function of expressing, the function of stating, the function of commanding, the function of informing, the function of praying, the function of begging, the function of requesting, the function of promising, and the function of rejecting. Illocutionary speech acts in song lyrics of Fabula album by Mahalini are relevant as Indonesian language teaching materials in high school, especially in poetry text teaching materials. The lyrics of this song can be used as a learning tool in determining the meaning contained in the poem.